2024
DOI: 10.3389/fimmu.2024.1356321
|View full text |Cite
|
Sign up to set email alerts
|

Manipulating the tumor immune microenvironment to improve cancer immunotherapy: IGF1R, a promising target

Marsha Pellegrino,
Valerio Secli,
Silvia D’Amico
et al.

Abstract: Cancer immunotherapy has made impressive advances in improving the outcome of patients affected by malignant diseases. Nonetheless, some limitations still need to be tackled to more efficiently and safely treat patients, in particular for those affected by solid tumors. One of the limitations is related to the immunosuppressive tumor microenvironment (TME), which impairs anti-tumor immunity. Efforts to identify targets able to turn the TME into a milieu more auspicious to current immuno-oncotherapy is a real c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 105 publications
0
2
1
Order By: Relevance
“…Findings from our study were consistent with those in previous studies and further revealed that miR-30a-3p, acting as a tumor suppressor, was directly sponged and downregulated by circ_PPAPDC1A, with upregulation of IGF1R and activation of IGF1R/PI3K/ AKT/mTOR signaling. However, there are also study [ 41 ] indicates that LINC01436 promotes NSCLC progression by functioning as a miR-30a-3p sponge to regulate the expression of its target gene EPAS1.However, our study indicates that there is no significant difference in the expression of EPAS1 in Osimertinib resistance cells and it has no significant impact on the sensitivity to Osimertinib. So, we believe that EPAS1 may be involved in the occurrence of NSCLC through miR-30a-3p, but its impact on Osimertinib resistance is minimal.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…Findings from our study were consistent with those in previous studies and further revealed that miR-30a-3p, acting as a tumor suppressor, was directly sponged and downregulated by circ_PPAPDC1A, with upregulation of IGF1R and activation of IGF1R/PI3K/ AKT/mTOR signaling. However, there are also study [ 41 ] indicates that LINC01436 promotes NSCLC progression by functioning as a miR-30a-3p sponge to regulate the expression of its target gene EPAS1.However, our study indicates that there is no significant difference in the expression of EPAS1 in Osimertinib resistance cells and it has no significant impact on the sensitivity to Osimertinib. So, we believe that EPAS1 may be involved in the occurrence of NSCLC through miR-30a-3p, but its impact on Osimertinib resistance is minimal.…”
Section: Discussioncontrasting
confidence: 57%
“…Insulin-like growth factor-1 receptor (IGF1R) is a transmembrane tyrosine-protein kinase (TPK) receptor that primarily binds with the ligand insulin-like growth factor-1 (IGF-1). This binding trigger conformational changes and autophosphorylation of specific tyrosine residues, initiating signal transduction pathways that play a crucial role in cell proliferation, adhesion, transformation, and apoptosis [ 41 ]. Current research [ 42 ] indicates that IGF-1R is highly expressed in various tumors and functions as an oncogene in the development and progression of cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In the field of oncology, the insulin-like growth factor 1/insulin-like growth factor 1 receptor (IGF1/IGF1R) axis stands out as one of the most extensively studied pathways [8,9]. From a molecular point of view, IGF1 binds to IGF1R, triggering its intracellular kinase activity.…”
Section: Introductionmentioning
confidence: 99%